The impact of Algerien migrants remittances on economie growth: an ARDL bound test approch - necib, amira; KERRACHE, Amar (Journal of Excellence for Economics and Management Research, 2025)
This study aims to measure the impact of Algerian migrants’ remittances on economic growth during the period from 1980 to 2023, in comparison with foreign direct investment (FDI), exports, and government expenditure. The Autoregressive Distributed Lag (ARDL) model is used to determine the short and long-term relationships between Algeria’s GDP, which measures economic growth, and migrant remittances, foreign direct investment (FDI), exports, and government spending (gex). The results of the study show that, such as government spending, migrant remittances have a negative long- and short-term impact on GDP and, on overall economic growth. Exports and foreign direct investment, on the other hand, show a favorable effect. These findings demonstrate how urgently Algeria must establish a suitable institutional structure and put laws into place that guarantee the best possible use of remittances in order to promote economic expansion.